ECONOMIC IMPACTS OF ROBOTICS TECHNOLOGY IN REMOTE GREENHOUSE FARMING: EVIDENCE FROM NORTHWEST INDIANA (International Journal of Innovative Technologies in Economy, 2026)
This study examines the economic impacts of robotics adoption in greenhouse farming, focusing on Northwest Indiana (NWI) as part of the U.S. Economic Development Administration’s Project TRAVERSE. The research aims to quantify how robotics and automation enhance productivity, reduce labor dependence, and generate regional economic benefits. Employing an input–output (I–O) modeling framework using IMPLAN 2022 data, the study estimates the direct, indirect, and induced impacts of investments in greenhouse and robotics sectors. Findings indicate that robotics adoption yields higher multipliers for output, employment, labor income, and value added compared to traditional greenhouse farming. These results highlight stronger regional linkages, increased efficiency, and sustainable employment opportunities. The analysis demonstrates that technological innovation in agriculture not only boosts productivity but also contributes to broader regional resilience and economic diversification. The paper concludes that systematic economic impact assessment is vital for guiding public investments, workforce development, and policy decisions. Future research should track long-term adoption trends, evaluate policy incentives, and integrate sustainability metrics to inform climate-resilient and inclusive agricultural innovation.